TESTING PECKING ORDER HYPHOTHESIS : FOOD & BAVERAGE INDUSTRIES YANG TERDAFTAR DI BURSA EFEK JAKARTA - Priyo Darmawan (Universitas Bunda Mulia, 2017)
This research paper is to analyze and to test capital structure and its impacted factors on the food and beverages listed companies at Indonesia Stok Exchange. The objective of this research is to test whether the variables of tangibility, firms size, profitability, growth opportunity, and financing deficit to impact on capital structure, and to address Pecking Order Hyphothesis or not. Sample are used i.e. companies are actively traded their shares at Indonesia Stock Exchange from the period of 2004-2009 . They also issue their comprehensive financial statements and at their domiciles in sourrounding Jakarta. During that periods, no merger and acquisition are taken place on that sample. Then selected companies sample are Aqua, Ades, Davomas, Delta Jakarta, Mayora, Multi Bintang, and Indofood Sukses Makmur through purposive sampling method. In this research paper that dependent variables is Capital Structure (DTA), while independent variables are Tangibility of Assets (FTA), Firm Size (SIZE), Profitability (NPM), Growth Opportunity, and Financing Deficit. The results of this paper is tangibility, profitability and financing deficit are only significantly impacted, whiles two others variables are not significantly impacted on Capital Structure. All independent variables impacted to dependent variables, Capital Structure is 79 %.Key words : Tangibility of Assets, Firm Size, Profitability, Growth Opportunity, Financing Deficit dan Capital Structure.